Application of sol–gel hybrid extraction sorbent for gas chromatographic analysis of organophosphorus pesticides - Wan Ismail, Wan Norfazilah (2016)
Sol–gel hybrid extraction sorbent based on methyltrimethoxysilane-cyanopropyltriethoxysilane (MTMOS-CNPrTEOS) was successfully synthesized by sol–gel process for use in solid-phase extraction (SPE) of organophosphorus pesticides (OPPs). Analysis was performed using gas chromatography–mass spectrometry. Several important sol–gel parameters were optimized. Fourier transform infrared spectroscopy, scanning electron microscopy and surface area analyses were used to characterize the composite structure and morphology in detail. The results showed that the specific area of sol–gel hybrid MTMOS-CNPrTEOS was 585 m2g−1 with perfect spherical shape with average size of 174 nm. Under the optimum sol–gel conditions (2:1 mol composition of MTMOS:CNPrTEOS, NH4OH of pH 10.5 and drying temperature of 100 °C), the method using MTMOS-CNPrTEOS SPE showed good linearity with excellent limit of detection (10–70 pg mL−1) at signal to noise ratio = 3 and good relative standard deviation (RSD < 9 %) for all the three OPPs analyzed.